2014
DOI: 10.1002/anie.201402011
|View full text |Cite
|
Sign up to set email alerts
|

Ester Carbonyl Vibration as a Sensitive Probe of Protein Local Electric Field

Abstract: The ability to quantify the local electrostatic environment of proteins and protein/peptide assemblies is key to yielding a microscopic understanding of many biological interactions and processes. Herein, we show that the ester carbonyl stretching vibration of two non-natural amino acids, L-aspartic acid 4-methyl ester and L-glutamic acid 5-methyl ester, is a convenient and sensitive probe in this regard since its frequency correlates linearly with the local electrostatic field for both hydrogen-bonding and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 48 publications
12
75
0
Order By: Relevance
“…This is because the YGGC*GG peptide, but not the YGGCGG peptide, gives rise to an IR band within the region of 1700-1750 cm 21 . 17 As expected, this ester carbonyl stretching vibrational band is broad and peaked at about 1720 cm 21 , which is similar to that observed for a short peptide containing a D M residue, due to hydrogen-bonding interactions with the solvent molecules. 17 In the second test of the cysteine alkylation strategy, we sought to incorporate the ME IR probe into two peptides that have been shown to form amyloid aggregates.…”
Section: Ester Incorporation Into Short Peptidessupporting
confidence: 83%
See 3 more Smart Citations
“…This is because the YGGC*GG peptide, but not the YGGCGG peptide, gives rise to an IR band within the region of 1700-1750 cm 21 . 17 As expected, this ester carbonyl stretching vibrational band is broad and peaked at about 1720 cm 21 , which is similar to that observed for a short peptide containing a D M residue, due to hydrogen-bonding interactions with the solvent molecules. 17 In the second test of the cysteine alkylation strategy, we sought to incorporate the ME IR probe into two peptides that have been shown to form amyloid aggregates.…”
Section: Ester Incorporation Into Short Peptidessupporting
confidence: 83%
“…The study by Ivanova et al 27 indicated that the LVEALYL segment within the IB peptide can forms fibrils and may play an important role in the fibril formation of the full length insulin B chain. The second peptide correspond to a double mutant of Ab [16][17][18][19][20][21][22] (sequence: KCVK*FAE, hereafter referred to as the Ab peptide), with a cysteine at the 17 position and a lys-Nvoc (Fmoc-Lys(4,5-dimethoxy-2-nitro-benzyloxycarbonyl)-OH, K*) at the 19 position. Following the study of Measey and Gai, 28 the lys-Nvoc was used in this case to facilitate amyloid fibril formation.…”
Section: Ester Incorporation Into Short Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, by using a photoresponsive structural constraint, it is possible to initiate a folding or unfolding process from a well‐selected conformational state. To improve the structural resolution of folding kinetic studies, we believe that the following approaches, many of which have already been used to study the equilibrium structures of membrane peptides and proteins, are promising: using (1) a local vibrational mode, such as that arising from an isotopically‐labeled amide unit or an unnatural amino acid side chain, , and resonance Raman scattering of a Trp probe, to gain site‐specific structural and environmental information; (2) the coupling between two site‐specific vibrators to probe tertiary interactions; (3) multiple fluorophores to simultaneously probe conformational changes of the protein of interest in different regions; (4) multi‐fluorophore FRET to reveal correlated conformational motions; and (5) various nonlinear techniques, such as two‐dimensional infrared, second harmonic generation, and sum frequency generation spectroscopy.…”
Section: Summary and Perspectivesmentioning
confidence: 99%